Energy storage - Sahoo, Umakanta (Advances in renewable energy, 2021)
The world's energy landscape is very complex. Fossil fuels, especially because of hydraulic fracturing, are still a mainstay of global energy production, but renewable energy sources, such as wind, solar, and others, are increasing in importance for global energy sustainability. Experts and non-experts agree that the next game-changer in this area will be energy storage. Energy storage is crucial for continuous operation of power plants and can supplement basic power generation sources over a stand-alone system. It can enhance capacity and leads to greater security, including continuous electricity supply and other applications. A dependable energy storage system not only guarantees that the grid will not go down, but also increases efficacy and efficiency of any energy system. This volume in addresses all of these issues, laying out the latest advances and addressing the most serious current concerns in energy storage.